Influence of quenching medium on the dendrite morphology, hardness, and tribological behaviour of cast Cu–Ni–Sn spinodal alloy for defence application - Bipin Sankar; Karthik V Shankar; Vamu Sunil; Hemanth Kashyap S; Nikhil Nair; Adarsh A. Nair; Abhinav P M (Defence Technology, 2023)
Cu–Ni–Sn spinodal alloys (Spinodal bronze) are potential materials with robust applications in components associated with defence applications like bearings, propellers, bushes, and shafts of heavily loaded aircraft, off-road vehicles, and warships. This paper presents a comparative study using water, Brine solution, and SAE 40 oil as the quenching media in regular bronze (Cu–6Sn) and spinodal bronze (Cu–9Ni–6Sn) alloys. Morphological analysis was conducted by optical microscopy, transmission electron microscopy (TEM), and X-ray diffraction technique (XRD) on bronze and spinodal bronze samples immersed in the three different quenching media to understand the grain size and hardness values better. Tribological analysis was performed to analyze the effect of quenching media on the wear aspects of bronze and spinodal bronze samples. The hardness value of the brine-aged spinodal bronze samples was as high as 320 Hv, and the grain size was very low in the range of 60 μm. A quantitative comparison between brine-aged regular bronze and brine-aged spinodal bronze showed that the hardness (Hv) was almost 80% higher for brine-aged spinodal bronze. Further, the grain size was approximately 30% finer for spinodal bronze when compared with regular bronze. When the load was increased in spinodal bronze samples, there was an initial dip in wear rate followed by a marginal increase. There was a steady increase in friction coefficient with a rise in load for brine-aged regular bronze and spinodal bronze samples. These results indicate that brine solution is the most effective quenching medium for cast Cu–Ni–Sn spinodal alloys.